PENERAPAN PEMBELAJARAN MATEMATIKA REALISTIK INDONESIA (PMRI) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS I SD NEGERI 011 BUKIT GAJAH KECAMATAN UKUI KABUPATEN PELALAWAN - Ipi Hanapiati (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2016)
This research was motivated by the low mathematics learning outcomes of students. Out of 35 students, only 15 students (40.54%) achieved learning mastery, with an average score of 68.65. This study aimed to improve students’ mathematics learning outcomes through the application of the Indonesian Realistic Mathematics Education (PMRI) approach. This research was a Classroom Action Research (CAR) conducted in two cycles. Based on the results of the study, both learning outcomes and learning activities of teachers and students showed improvement in each cycle. Teacher activities increased from Cycle I Meeting I with a score of 14 (70%) to Cycle I Meeting II with a score of 15 (75%). In Cycle II Meeting I, the score increased to 17 (85%) and further increased to 18 (90%) in Cycle II Meeting II. Student activities also improved, where in Cycle I Meeting I the score obtained was 12 (60%), increasing to 16 (80%) in Cycle I Meeting II. In Cycle II Meeting I, student activity reached a score of 17 (85%) and remained at 17 (85%) in Cycle II Meeting II. Furthermore, students’ mathematics learning outcomes improved significantly. The initial average score of 68.65 increased in Cycle I to an average score of 95.41 and further increased in Cycle II to 97.97. It can be concluded that the application of the PMRI approach can improve students’ mathematics learning outcomes.